Nudging physical activity in offices. Issue 4 (2nd September 2019) - Van der Meiden, Iris; Kok, Herman; Van der Velde, Gerben
Abstract : Purpose: This paper aims to investigate whether and why nudging interventions in an office environment are effective to stimulate stair use of employees. Design/methodology/approach: This paper is based on a pre-test/post-test case study design at the headquarters of a Dutch online retailer. Observations were conducted to test the impact of two nudge interventions, being footprints and posters, on employees' stair use in two consecutive pre-test/post-test weeks. An online survey questionnaire was used to assess employees' overall experience with the nudging interventions after the fifth and again neutral week. Findings: A total of 14, 357 observations were recorded during five weeks. This research shows that footprints as nudging intervention significantly increase stair use of employees, and after removal, significantly decrease stair use again. Moreover, footprints were more effective than posters, of which the latter did not impact stair use significantly. Results from the survey questionnaire, completed by 46.2 per cent of the employees, showed that, in terms of degree of perception, footprints (91.4 per cent) were more noticeable than posters (46.3 per cent). Originality/value: This paper contributes to the non-conclusive research regarding the effectiveness of nudging interventions on stair use in office environments. It clearly shows that perceptibility in combination with a positive attitude towards the nudge leads to a higher degree of initial behavioural change, yet not to a change of mind.